Pengaruh Ekonomi Makro terhadap Volatilitas Return Indeks Saham Konvensional dan Syariah - Lia Zulfa Laila; Hasbi Assidiki Mauluddi; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The high number of actors investing in the stock market requires investors to have understanding and information about the rate of return and risk that will occur. For this reason, investors need to know what predictable factors can affect stock returns. Therefore, this study aims to determine the effect of inflation, exchange rates, BI rates, and foreign exchange reserves on return volatility of conventional and sharia stock indexes. The type of data used is secondary quantitative data from the Indonesia Stock Exchange, Bank Indonesia, the Central Bureau of Statistics, Google Finance. The population in this study is the conventional and sharia stock index. Sample data determined by purposive sampling method. This study uses the Panel Data Regression Analysis model with a combination of time series and cross section data to see the effect of the independent variables on the dependent variable. The data processing aids used in this study were Microsoft Excel 2010 and Eviews version 10. The results of the study found that conventional stock index return volatility for inflation had a negative and significant effect, the BI Rate had a negative and insignificant effect, the exchange rate had a positive and significant effect and device backup has a negative and significant effect. Whereas on the return volatility of the sharia stock index for the inflation variable has a negative and significant effect, the Bi Rate has a negative and significant effect, the exchange rate has a positive and significant effect, and foreign exchange reserves have a negative and insignificant effect.